Analysis of Internal Control on Cash Receiving (Case Study at the Pratama Tiara Bunda Clinic) - Endah Prawesti Ningrum; Nita Komala Dewi; Matdio Siahaan; Dea (Future Science, 2022)
This study aims to make Tiara Bunda Clinic able to understand and evaluate internal control in the purchasing system that has been implemented. This type of research is a case study at the Pratama Tiara Bunda Clinic, with data collection techniques used are interviews and documentation. The results of this study can be concluded that the internal control system for cash receipts at Tiara Bunda Clinic Pratama for the risk assessment component and control activities are not adequate with COSO 2013 this is evident from the practice implemented by Tiara Bunda Clinic Pratama. This difference is because there have not been any changes at all related to regulations or the operating environment relating to cash receipts and physical control of cash receipts assets at the clinic every time a deposit is made to the clinic owner, it is always recalculated, for computer programs related to cash receipts assets there data in non-computerized cash receipts, only patient data is computerized. Meanwhile, the components of internal control, information, and communication, as well as monitoring are by the 2013 COSO theory, This can be proven from the practice that has been carried out by Tiara Bunda Clinic.